Screening for mutations in selected miRNA genes in hypogonadotropic hypogonadism patients - Anna-Pauliina Iivonen (Endocrine Connections, 2019)
In approximately half of congenital hypogonadotropic hypogonadism (cHH) patients, the genetic cause remains unidentified. Since the lack of certain mi RNAs in animal models has led to cHH, we sequenced human miRNAs predicted to regulate cHH-related genes (MIR7-3, MIR141, MIR429 and MIR200A-C) in 24 cHH patients with Sanger sequencing. A heterozygous variant in MIR200A (rs202051309; general population frequency of 0.02) was found in one patient. Our results suggest that mutations in the studied miRNAs are unlikely causes of cHH. However, the complex interplay between miRNAs and their target genes in these diseases requires further investigations.